Kinetic Barrier Against Standing Up of Pentacene Molecules Upon a Pentacene Monolayer (Phys. Status Solidi RRL 8/2018). Issue 8 (8th August 2018) - Zhang, Lei; Huo, Shuchun; Fu, Xing; Hohage, Michael; Sun, Lidong
Abstract : Lei Zhang et al. (article no. 1800230 ) report on the growth of pentacene thin films on the Cu(110)‐(2×1)O surface as a function of substrate temperature. In particular, reflectance difference spectroscopy (RDS) has been applied in‐situ to monitor the orientation of the pentacene molecules during the growth and subsequent annealing. Deposition at a substrate temperature of 230 K results in a lying‐down orientation for all pentacene molecules. Subsequent annealing to a temperature of 350 K induces reorientation for molecules above the first monolayer into a standing‐up configuration. By a quantitative analysis on the corresponding evolution of the RD signals, the kinetic barrier of the reorientation of a pentacene molecule from lying‐down to standing‐up has been determined to be 970 ± 150 meV with an associated attempt frequency in the order of 10 14 Hz. The system studied is rather general for organic thin film growth involving an intermediately weak molecule–surface interaction and the energy barrier determined here should thus be representative.